Edukasi Petani dalam Penanggulangan Hama Tanaman dengan Pestisida Nabati Kulit Bawang Merah - Darsan Darsan; Yudha, Danang Ananda; Yusdiantara Yusdiantara; Zahra Amelia (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Using plant-based pesticides is a good step for agriculture that is more environmentally friendly than chemical pesticides. Vegetable pesticides are more natural and safer for the environment than chemical pesticides because they are made from natural ingredients. The impacts that will be felt if the use of chemical pesticides continues will have an impact on animals and humans. Chemical pesticides have the most significant effect, namely causing the death of several other animals besides organisms. In addition, exposure to chemical pesticides also has significant effects on human health. Achievements in this community service can increase knowledge about pest control by using vegetable pesticides from onion skins which can be used as natural pesticides and the community can switch from using chemical pesticides to vegetable pesticides which are more environmentally friendly.